TRLS-09. RTOG1119: PHASE II RANDOMIZED STUDY OF WHOLE BRAIN RADIOTHERAPY / STEREOTACTIC RADIOSURGERY IN COMBINATION WITH CONCURRENT LAPATINIB IN PATIENTS WITH BRAIN METASTASIS FROM HER2-POSITIVE BREAST CANCER. (12th August 2019) - Kim, In Ah; Winter, Kathryn; Peereboom, David; Sperduto, Paul; De Los Santos, Jennifer; Ogunleye, Tomi; Boulter, Daniel; White, Julia; Mehta, Minesh
Abstract: The addition of trastuzumab to cytotoxic chemotherapy has improved outcomes for patients with HER2 positive breast cancer. Increased survival coupled with limited blood-brain barrier (BBB) penetration of trastuzumab may contribute to the increased incidence of brain metastasis in these patients. Half of these patients die of intracranial disease progression rather than extracranial disease. Therefore, strategies to improve survival must include increased CNS disease control in these patients. Lapatinib crosses the BBB and demonstrates modest activity against intracranial metastases. Based upon preclinical data and results of a phase I study, we hypothesized that lapatinib plus WBRT /SRS can improve the intracranial disease control compared to WBRT / SRS alone. A randomized phase II trial of WBRT (37.5 Gy/3 weeks) or SRS plus or minus concurrent lapatinib (daily 1000 mg for 6 weeks) was initiated. CNS penetrating HER2 targeted therapy is permitted throughout the study, but patients not on trastuzumab, pertuzumab or any other breast cancer therapy at study entry are not permitted to begin this therapy while on protocol treatment, but may begin it 24 hours after completion of protocol treatment. Eligibility includes HER2+ breast cancer with at least one measurable, unirradiated parenchymal brain metastasis. The two populations targeted for accrual include patients with 1) newly diagnosed, multiple brain metastases or 2) progressive brain metastases after stereotactic radiosurgery (SRS) or surgical resection of 1–3 metastases. Prior lapatinib is allowed. Patients are stratified by breast-specific graded prognostic assessment; use of non-CNS penetrating HER2 targeted therapy; and prior SRS or surgical resection. The primary endpoint is complete response rate in the brain 12 weeks after WBRT. Secondary endpoints include objective response rate, lesion-specific response rate, CNS progression-free survival, and overall survival. 140 of 143 target accrual have enrolled (4/22/2019).